The incidence, presentation, outcomes, risk of mortality and economic data of drug-induced liver injury from a national database in Thailand: A population-base study - Sobhonslidsuk, A; Poovorawan, K; Soonthornworasiri, N; Pan-Ngum, W; Phaosawasdi, K (BioMed Central, 2016)
Background Toxic liver diseases are mainly caused by drug-induced liver injury (DILI). We assessed incidences and outcomes of DILI including associated factors for mortality. Methods We performed a population-based study of hospitalized patients with DILI. Information was retrieved from the Nationwide Hospital Admission Data using ICD-10 code of toxic liver diseases (K71) and additional codes (T36–T65). The associated factors were analyzed with log-rank test, univariate and multiple cox regression analysis. Results During 2009–2013, a total of 159,061 (average 21,165 per year) admissions were related to liver diseases. 6,516 admissions (1,303 per year) were due to toxic liver diseases. The most common type of toxic liver disease was acute hepatitis (33.5 %). In-hospital and 90-day mortality rates were 3.4 % and 17.2 %. DILI with cirrhosis yielded the highest in-hospital and 90-day mortality rates (15.8 % and 47.4 %). Acetaminophen, cirrhosis and age ≥ 60 years were seen in 0.5 %, 8.3 % and 50.1 % of patients who died versus 5 %, 2.3 % and 32.4 % of survivors. Factors associated with mortality were cirrhosis (HR 2.72, 95 % CI: 2.33–3.19), age ≥60 years (HR 2.16, 95 % CI: 1.96–2.38), human immunodeficiency viral infection (HR 2.11, 95 % CI: 1.88–2.36), chronic kidney disease (HR 1.59, 95 % CI: 1.33–1.90), chronic obstructive pulmonary disease and bronchiectasis (HR 1.55, 95 % CI: 1.17–2.04), malnutrition (HR 1.43, 95 % CI: 1.10–1.86) and male (HR 1.31, 95 % CI: 1.21–1.43). Acetaminophen DILI yielded lower risks of mortality (HR 0.24, 95 % CI: 0.13–0.42). The most common causes of DILI were acetaminophen (35.0 %) and anti-tuberculous drugs (34.7 %). Conclusions DILI is an uncommon indication for hospitalization carrying lower risks of death except in patients with non-acetaminophen, cirrhosis, elderly or concomitant diseases.